Comparison of serum aminotransferase between gas and gasless laparoscopy cholecystectomy - Agus Barmawi, Imam Sofii Hendro Wartatmo (Universitas Gadjah Mada, 2010)
Carbondioxide (CO2) insufflations in laparoscopy with gas will increase intraabdominal pressure that influences thehemodynamic, lungs, and kidneys. One of important hemodynamic changes is temporary reduction of hepatic bloodflowbecause of pneumoperitoneum. Pressure caused by pneumoperitoneumcan influence ischemia degree of hepaticcell and cause hepatic enzymes increase. Enzyme that includes in hepatic enzyme is aminotransferase,which consistsof: transaminase (AST) or glutamic oxaloacetic transaminase serum and alanine transaminase (ALT) or glutamicpyruvic transaminase serum. Laparoscopy method by lifting abdomen wall (gasless laparoscopy) without CO2insufflations can decrease the damaging effects of high intraabdominal pressure. This research was an experimentalresearch with single blind randomized clinical trial (RCT) plan, with observation of symptomatic cholelithiasis patientswho underwent cholecystectomy laparoscopic cholecystectomy with gas or CO2 (pneumoperitoneum) or withoutgas (gasless). Hepatic function tests were then held at 24 hours and 72 hours after operation. Research subjectswere symptomatic cholelithiasis patients who fulfilled inclusion and exclusion criteria. Samples needed were 24people in each group. The independent variable was patients with symptomatic cholelithiasis who underwentcholecystectomy laparoscoped with gas compared to those being cholecystectomy laparoscoped without gas. Thedependent variable was aminotransferase enzyme value before operation, and 24, 72 hours postoperation. The datawere analyzed using Kolmogorov Smirnov, independent t-test, pair t-test, and MannWhitney test. It was obtained21 cases for men (43.75%), 27 cases for women (56.25%). The average age of the group laparoscopy with gaswas 47.16Â±10.76 years old and the group laparoscopy without gas was 45.3Â±11.48 years old (p>0,05). Theaverage values of AST and ALT 24 hours postoperation of the group laparoscopy without gas were 21.9Â±7.6 U/L(increase 24%) and 26.3Â±5.2 U/L (increase 46%) compared to 65.8Â±18.4 U/L (increase 206%) and 62.8Â±14.3U/L (increase 280%) in the group laparoscopy with gas (p< 0,05). The average values of AST and ALT 72 hourspostoperation of the group laparoscopywithout gaswere 24.7Â±8.3 U/L (increase 33%) and 28.9Â±7.3 U/L (increase17%) compared to 71,5Â±28,6 U/L (increase 250%) and 75.8Â±16.9 U/L (increase 360%) in the group laparoscopywith gas (p< 0,05). In conclusion, there were significantly increases of serum aminotransferase values (AST andALT) in cholecystectomy laparoscopy with gas compared to in cholecystectomy laparoscopy without gas.Key words: cholecystectomy laparoscopy â pneumoperitoneum - gasless â serum aminotransferase